2018
DOI: 10.1111/cbdd.13325
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocortisone inhibition of wild‐type and αD200Q nicotinic acetylcholine receptors

Abstract: Short-term treatment with large doses of corticosteroids can result in acute weakness of muscles in processes that have not yet been fully characterized. Corticosteroids have been shown to exert direct inhibitory action on the muscle-type nicotinic acetylcholine receptor (AChR), and therefore can promote pharmacological muscle denervation. The mechanism of hydrocortisone (HC) blockage of AChR has not been fully established yet. It is uncommon for an electrically neutral molecule, for example, HC, to induce vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Even though it is necessary to perform more experiments to characterize in detail the polyamine-induced blocking mechanism that generates the 'reopening current', we propose that the phenomenon of a 'reopening current' is consistent with the mechanism proposed recently for blocking of the nACh receptor by hydrocortisone [17]. It was suggested that hydrocortisone was able to displace an agonist from its binding site.…”
Section: Discussionsupporting
confidence: 84%
“…Even though it is necessary to perform more experiments to characterize in detail the polyamine-induced blocking mechanism that generates the 'reopening current', we propose that the phenomenon of a 'reopening current' is consistent with the mechanism proposed recently for blocking of the nACh receptor by hydrocortisone [17]. It was suggested that hydrocortisone was able to displace an agonist from its binding site.…”
Section: Discussionsupporting
confidence: 84%
“…Conceptually, antibodies to the AChR (anti-AChR) must be presented in the circulation prior to the development of neurophysiological manifestations in subclinical patients (14). A surge in circulating glucocorticoid levels in response to acute stress may exert a direct inhibitory action on the AChR, and therefore can precipitate myasthenic symptoms (15). Glucocorticoids may exert contradictory effects on immune system depending on their concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold of the opening transition was set at one-half of the unitary current. Open dwell times were calculated by fitting the probability density function (the sum of two exponential terms [ 45 ]) to open time histograms with the use of Clampfit. τ oi corresponds to the time constant of the i th component, P corresponds to its normalized area.…”
Section: Methodsmentioning
confidence: 99%